The role of m5C, m1A and m7G modifications in tumors of urinary system - Wei Xue; Yuanyuan Zhao; Gong Zhang; Zhiyuan Li; Jixin Li; Xiang Fei (Frontiers in Cell and Developmental Biology, 2025)
Malignant tumors of the urinary system, such as kidney cancer, bladder cancer, and prostate cancer, remain a significant challenge despite the various treatment options available. Identifying therapeutic targets for urological tumors is crucial due to the potential for recurrence and metastasis. Recent research has highlighted the importance of RNA modifications in post-transcriptional regulation, impacting various biological functions in urological tumors, including tumorigenesis, progression, metastasis, and drug resistance. However, the specific mechanisms underlying these interactions are not fully understood. This review will focus on exploring the regulatory role of RNA modifications like m1A, m5C, and m7G in urological tumors, shedding light on the pathways and molecular mechanisms involved. This analysis aims to provide new insights for the treatment of urological tumors.